KEJADIAN ASFIKSIA BERDASARKAN USIA KEHAMILAN DI RSUD DR. WAHIDIN SUDIRO HUSODO KOTA MOJOKERTO - Frilasari, Heni; Triwibowo, Heri (JURNAL KEPERAWATAN SEHAT, 2016)
The incidence of neonatal asphyxia in newborns in Indonesia tends to increase. Infants less than one month of age is the age group that has the highest risk of health problems, such as asphyxia. Asphyxia in newborns can be caused by various factors, one of which is pregnancy. In premature infants frequent respiratory disorder caused by a deficiency of surfactant, lung growth and development of the rudimentary thus increasing the risk of asphyxia. The purpose of the research was to determine the incidence of asphyxia by gestation in dr. WahidinSudiroHusodo Hospital, Mojokerto City. The descriptive research design. The population is all newborns were asphyxiated in dr. WahidinSudiroHusodo Hospital, Mojokerto City many as 22 infants to obtain a sample of 22 respondents taken with total sampling. The research variables are based on gestational age asphyxia. The collection of data through observation of asphyxia, after the data is collected to analyze the data by editing, coding, scoring and tabulating. The results showed that the majority of newborn asphyxia were as many as 19 infants (86.4%) on gestational age <37 weeks. The younger the gestational age, organ function less and less perfect baby which can cause asphyxia. Women should be able to perform routine prenatal care, so that if there are complications or complications of treatment can be done in a comprehensive manne.Keywords: Asphyxia, Age Pregnancy